Low loss Type II regenerative Bragg gratings made with ultrafast radiation - Grobnic, Dan; Hnatovsky, Cyril; Mihailov, Stephen J (Optics express, 2016)
A novel type of fiber Bragg grating is produced by annealing a type I-like grating that is written with multiple infrared femtosecond laser pulses through a phase mask under conditions that are typically used to fabricate thermally stable type II gratings. This new grating is created through a process similar to a regenerative one and displays low loss and high resilience in a 1000 °C ambient environment. Such gratings are ideally suited for quasi-distributed sensing at high temperatures.